The concept of the Enterprise and its adaptation criteria within the competition law - Azouz, Karima (Journal of Human Sciences, 2021)
This study aims to identify the concept of the enterprise and the criteria for its adaptation under the competition law, as we find that modern competition legislation has expanded this concept depending on the economic activity practiced by the intervener in the market, regardless of its class and legal form.This is what the Algerian legislator went to, so he subjected all natural and moral persons, as well as organizations, unions and associations, beside public persons to the provisions of the competition law, whenever the entity practiced economic activity, and this was in order to protect the principle of competition in the market, so the institution is considered the first pillar in the competitive market and without it there is no Market in the sense of competition law. The legislator has also expanded the concept of economic activity practiced by it, thus subjecting all activities that appear in the market to the competition law, including public deals.